Hanuman Langur Semnopithecus dussumieri feeding on the apical stem of Euphorbia nivulia at Mount Abu and Kumbhalgarh Wildlife Sanctuaries in Rajasthan, India - Sharma, Satish Kumar; Koli, Vijay Kumar (Journal of the Bombay Natural History Society (JBNHS), 2014)
No Abstract.